CHANGES IN THE GENERAL SECONDARY EDUCATION SYSTEM IN THE KASHKADARYA REGION IN 1924-1945. - Ne`matov Shavkatjon is the son of Boymurad (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract.  This  article  is  devoted  to  the  changes  in  the  general  secondary education  system  in  the  Kashkadarya  region  in  1924-1945  and  the  attitude  to  the education sector.